Psycholinguistic Analysis of Sylvia Plath’s Mental State and its Expression in “The Arrival of the Bee Box” - Mr. Asif Ali; Dr Irfan Abbas; Azeem Alphonce, (Al-Mahdi Research Journal (MRJ), 2024)
This study explores Sylvia Plath’s The Arrival of the Bee Box through the lens of psycholinguistics, employing Conceptual Metaphor Theory and Cognitive Linguistics to analyze the interplay of language, imagery, and mental states. Addressing two key research questions, it examines how Plath’s linguistic strategies including metaphorical language and repetition mirror her emotional conflicts and psychological turmoil. The central metaphor of the bee box symbolizes the containment of unconscious thoughts, reflecting the tension between the narrator’s conscious control and the chaotic forces of the unconscious. Additionally, the sensory and spatial imagery bridges the divide between embodied cognition and abstract thought, illustrating the intricate relationship between conscious and unconscious mental processes. This analysis underscores the role of language as a mediator between inner experience and external expression, revealing how Plath externalizes and negotiates her inner conflicts through linguistic and cognitive strategies.